Growth performance and yield production of cherry tomato as affected by media types and grown under different greenhouse systems - Mohmad Hairin, Nur Eastiharah; Sakimin, Siti Zaharah; Ramlan, Mohd Fauzi; Baghdadi, Ali; Mat Su, Ahmad Suhaizi; Dahlan, Nofri Yenita (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
To produce a good quality of tomato, it must be grown in proper media to avoid pests and diseases and to optimize the consumption of agriculture waste material for beneficial crops production. The proper media will be acted as good anchorage to plants and supply nutrients and gaseous exchange to root. Meanwhile, the climate changes also one the serious issue that can reduce the tomato production. The optimum environment inside the greenhouse for the tomato plant to grow well warrants should be investigated. Thus, this study is to investigate the effectiveness of three types of media (coconut coir dust, mixed soil and topsoil) on growth performance and yield of tomato cherry grown under two systems of the greenhouse which are smart greenhouse system (SGS) and conventional greenhouse system (CGS). The experiment was conducted in 2 factorials in a nested design with four replications. Growth performance and the total weight of yield were monitored. Results indicated that the plant height, root length and yield production of cherry tomato were higher when the plant is grown in coconut coir dust as compared to other treatments.